Glycoalkaloids in peels of Indian potatoes - Singh, Brajesh (Potato Journal, 2016)
Glycoalkaloids are unwanted potato constituents for consumers since they are toxic to human beings. In general potato peels contain high content of glycoalkaloids compared to flesh. Samples of peel from forty one Indian potato cultivars were analyzed for α-solanine and α-chaconine content by High Performance Liquid Chromatography. In Indian potatoes, α-solanine content ranged from 13.67 (Kufri Kundan) to 186.13 µg/mg FW (Kufri Chamatkar) with an average content of 76.37 µg/mg FW. α-chaconine content ranged from 10.96 to 199.85 µg/mg FW with the lowest values exhibited by Kufri Kundan and the highest by Kufri Neela. The average α-chaconine content in peels was 86.18 µg/mg FW. Average total glycoalkaloids content was 161.74 µg/mg FW with the lowest value exhibited by Kufri Kundan (24.41 µg/mg FW) and the highest by Kufri Badshah (362.18 µg/mg FW). Cultivars Kufri Chipsona-1, Kufri Chipsona-3 and Kufri Jyoti also contained low contents of glycoalkaloids (58.87, 57.99 and 77.89 µg/mg FW, respectively). Potato varieties should not contain more than 20mg of glycoalkaloids per 100g of fresh weight, though, the content of glycoalkaloids was much higher than the given limit in peels of Indian potatoes. However, in most of the potato based recipes, potatoes are used after peeling in India, therefore there are less chances of toxicity by glycoalkaloids from potatoes.